Ogilvie’s Syndrome Post Elective Caesarean Section - Eugenius Phyowai Ganap; Annisa Fitriani; Andhyta Ratih Wulandari (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Ogilvie's syndrome is an acute abdominal condition characterized by massive colonic distension without any evidence of mechanical obstruction. In female patients this syndrome was associated with caesarean section and the use of spinal anaesthetics.Case: We report a case of Ogilvie's syndrome that occurred after elective caesarean section. On the first day postoperative care the patient complained of lower abdominal pain accompanied by abdominal bloating. Physical examination reveals a distended abdomen without clinical evidence of peritonitis. Vital signs were normal and laboratory results showed an increase in leukocytes. An abdomen radiology was taken and shows gas distention in the large intestine which did not decrease even after given muscle relaxants. The patient then underwent emergency surgery by digestive surgeon followed by decompression measures for intestinal distention. The patient got a good postoperative care and continued control through the outpatient clinic.Discussion: The exact mechanism that causes colonic dilatation in Ogilvie's syndrome is not known clearly, but many of these cases are associated with trauma, spinal anaesthesia, and pharmacological agents in which the autonomic nervous system (ANS) function is impaired. Diagnosis can be made by abdominal imaging which will show dilation of the large intestine. The main goal of treatment is to decompress the colon and thereby minimize the risk of colonic ischemia, perforation, and death. Pharmacological therapy should be considered in patients who fail conservative management within 24-48 hours, with the last resort being colonic decompression up to laparotomy with or without stoma creation.Conclusion: Although it has a rare incidence, Ogilvie's syndrome has a high morbidity and mortality rate. Proper management of Ogilvie's Syndrome is carried out according to an algorithm starting from conservative management, pharmacology, to surgical management in resistant cases.Key words: Ogilvie syndrome; acute abdomen; caesarean section complication.